The Validity of Electronic Agreements in the Perspective of Indonesian Civil Law - Febrihadi Suparidho; Septira Putri Mulyana (Universitas Muhammadiyah Palu, 2025)
The development of information and communication technology has given rise to various new forms of legal relationships in society, one of which is electronic contracts. In classical civil law, agreements are always associated with written forms and physical signatures. However, the digital era demands a reinterpretation of civil law principles to maintain their relevance. This study aims to analyze the validity of electronic agreements from the perspective of Indonesian civil law, by examining the relationship between the Civil Code (KUHPerdata) and Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE). The research method used is normative juridical with a statutory and conceptual approach. The results indicate that electronic agreements have the same legal validity as written agreements as long as they meet the requirements for a valid agreement as stipulated in Article 1320 of the Civil Code and the provisions for valid electronic documents as stipulated in Article 5 of the UU ITE. However, challenges remain in terms of evidence and legal protection for parties in electronic transactions.